2015
DOI: 10.1007/s12035-015-9207-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidized Cholesterol in Diabetes-Induced Lysosomal Dysfunction in the Brain

Abstract: Abnormalities in lysosomal function have been reported in diabetes, aging, and age-related degenerative diseases. These lysosomal abnormalities are an early manifestation of neurodegenerative diseases and often precede the onset of clinical symptoms such as learning and memory deficits; however, the mechanism underlying lysosomal dysfunction is not known. In the current study, we investigated the mechanism underlying lysosomal dysfunction in the cortex and hippocampi, key structures involved in learning and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 59 publications
2
18
0
2
Order By: Relevance
“…Treatment with various cathepsin inhibitors indicate that release of cathepsin D from these cells appears to drive GLT-induced cell death. These findings are consistent with recent studies showing lysosomal dysfunction and LMP in the renal tubule and neuronal cortex when exposed to elevated lipid concentrations (41,42). The finding that human type 2 diabetic tissue shows defects in both autophagic flux (p62 accumulation) and lysosomal function (cathepsin D staining) strongly supports a role for lysosomal/autophagic-induced cell death as a major driver of b-cell death and dysfunction in type 2 diabetes.…”
Section: Jnk Mediates Glt-induced Autophagy But Not Lysosomal Dysfuncsupporting
confidence: 92%
“…Treatment with various cathepsin inhibitors indicate that release of cathepsin D from these cells appears to drive GLT-induced cell death. These findings are consistent with recent studies showing lysosomal dysfunction and LMP in the renal tubule and neuronal cortex when exposed to elevated lipid concentrations (41,42). The finding that human type 2 diabetic tissue shows defects in both autophagic flux (p62 accumulation) and lysosomal function (cathepsin D staining) strongly supports a role for lysosomal/autophagic-induced cell death as a major driver of b-cell death and dysfunction in type 2 diabetes.…”
Section: Jnk Mediates Glt-induced Autophagy But Not Lysosomal Dysfuncsupporting
confidence: 92%
“…Unlike non-oxidized LDL that accumulates in lysosomes of NPC mice, recent evidence points toward the specific lysosomal trapping of oxLDL in Ldlr −/− mice and in cultured macrophages [ 5 , 17 , 19 , 20 ]. Besides NAFLD, increasing attention has been directed to the crucial role of oxLDL in the pathogenesis of various metabolic diseases, including atherosclerosis [ 7 ] and diabetes [ 21 ]. However, thus far, oxLDL has been shown to be highly resistant to removal from the lysosome [ 22 ] and to intracellular degradation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ganglioside GM3 is a primary or secondary storage product in many LSDs, and, owing to its role in the modulation of insulin sensitivity and energy homeostasis (Aerts et al, 2011), its storage can reduce insulin signalling, as was demonstrated in GD (Langeveld et al, 2008). In cells and tissues of patients and animal models of diabetes, alterations in lysosome function, such as intralysosomal phospholipid accumulation and autophagy insufficiency, contribute to the etiology of the disease (Sims-Robinson et al, 2016;Yamamoto et al, 2017;Yasuda-Yamahara et al, 2015). Specifically, β-cells under starvation degrade secretory insulin granules in a protein kinase D-dependent manner after their recruitment to lysosomes (Goginashvili et al, 2015).…”
Section: Diabetesmentioning
confidence: 99%